Labor market effects of sports and exercise: Evidence from Canadian panel data - Michael Lechner; Nazmi Sari (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Based on the Canadian National Population Health Survey we estimate the effects of individ-ual sports and exercise on individual labor market outcomes. The data covers the period from 1994 to 2008. It is longitudinal and rich in life-style, health, and physical activity in-formation. Exploiting these features of the data allows for a credible identification of the effects as well as for estimating dose-response relationships. Generally, we confirm previous findings of posi tive long-run income effects. However, an activity level above the current recommendation of the WHO for minimum physical activity is required to reap in the long-run benefits.
Keywords: I12; I18; L83; 330